More answers

The expression (9x 7)-(x 3) can be simplified as follows: (9x - 7) - (x - 3) = 9x - 7 - x + 3 = 8x - 4

Q: What is (9x 7)-(x 3)?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

- 7x + (9x - 3) = - 7x + 9x - 3 = 2x - 3

9x-8=7x-3 9x-7x=-3+8 2x=5 x=5/2 x=2.5

Simplifying 2x + 3 = 9x Reorder the terms: 3 + 2x = 9x Solving 3 + 2x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 3 + 2x + -9x = 9x + -9x Combine like terms: 2x + -9x = -7x 3 + -7x = 9x + -9x Combine like terms: 9x + -9x = 0 3 + -7x = 0 Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 or x = 3/7 Simplifying x = 0.4285714286 or x = 3/7

7x = 4x - 93x = -9x = -3

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

Related questions

- 7x + (9x - 3) = - 7x + 9x - 3 = 2x - 3

9x-8=7x-3 9x-7x=-3+8 2x=5 x=5/2 x=2.5

2x+3=9x 3=9x-2x 3=7x x=3/7

Simplifying 2x + 3 = 9x Reorder the terms: 3 + 2x = 9x Solving 3 + 2x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 3 + 2x + -9x = 9x + -9x Combine like terms: 2x + -9x = -7x 3 + -7x = 9x + -9x Combine like terms: 9x + -9x = 0 3 + -7x = 0 Add '-3' to each side of the equation. 3 + -3 + -7x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = 0 + -3 -7x = 0 + -3 Combine like terms: 0 + -3 = -3 -7x = -3 Divide each side by '-7'. x = 0.4285714286 or x = 3/7 Simplifying x = 0.4285714286 or x = 3/7

7x - 9x = -2x

7x = 4x - 93x = -9x = -3

9x-3y=63 7x-3y=45 -3y=63-9x -y=21-3x y=-21+3x 7x-3(-21+3x)=45 7x+63+9x=45 7x+9x=45-63 16x=-18 x=-1.125 y=-21+3(-1.125) y=-24.375 (-1.125,-24.375)

7 plus 7x--2x plus 3 is: 7 + 7x + 2x + 3 = 0 9x + 10 = 0 9x = -10 x = -10/9 = -1 1/9

9x-4 = 7x+8 9x-7x = 8+4 2x = 12 x = 6

9x+6 = 7x+18 9x-7x = 18-6 2x = 12 x = 6

2x=7x=9x

If you mean: 7x-53 = 9x Then the solution is: x = -26.5